An Attempt to Reconstruct the Generation of Žemininkai: Benediktas Labėnas - Tūtlytė, Rita (Colloquia, 2022)
Benediktas Labenskas-Labėnas (1919–1949), a little-known literary figure from the Žemininkai generation, was a soldier and partisan, who died in the early post-war guerrilla warfare. The article presents a part of his work written in gymnasium, in military school and on the Eastern Front. It traces author’s evolution, discusses the relationship of his works to literary tradition, and highlights the distinctive nature of his themes and style. The research employs a hermeneutical approach, the perspective of the history of literature, and the socio-cultural aspect, which enable to identify the ideological and cultural reverberations of a specific historical time and their influence in the works of the young author. Labėnas’s oeuvre grows out of the neo-romantic tradition of 20th-century Lithuanian literature, the songs of volunteers and soldiers’ marching, as well as Christian culture. It takes root in social, psychological, and impressionistic prose. Labėnas’s work is characterized by a sense of harmony between the world and a human being, the imperative of the task of life, an ethical approach, and literary sense of genre and style that became increasingly pronounced with the time. On the one hand, Labėnas’s work has very little in common with the creative engagement of his generation, such as the inclination to existential questions and modern poetic language. On the other hand, his works are associated with a strong connection with the earth and reflection on that connection.